A Practitioner's View of the Realization Concept. - Defliese, Philip L. (The Accounting Review, 1965)
As well known, the practitioner must operate within his own frame of reference that is, he can give recognition only to those economic changes which affect financial position and results of operations as determined by generally accepted accounting principles. Thus, he cannot stray far beyond the concepts that are presently understood and accepted by the business community or those that he believes could become acceptable. This does not mean that he cannot look forward to the day when the balance sheet and income statement will present financial position and results of operations in an absolute or economic sense. He must realize, however, that the latter is a different frame of reference, which is far from attainment. The report on the realization concept and the supplementary statements also appear to stress an objective of recognizing holding gains and losses resulting from increments and decrements in the value of assets as they occur, rather than postponing their recognition and inclusion in the measurement of income only at the time the asset is disposed of.